Investigation of magnesium aluminometasilicate (Neusilin US2) based surface solid dispersion of sorafenib tosylate using QbD approach: In vitro and in vivo pharmacokinetic study - Bijoy Kumar Panda; Bothiraja Chellampillai; Sharad Ghodke; Ashwin Mali; Ravindra Kamble (International Association of Physical Chemists (IAPC), 2024)
Background and purpose: Sorafenib tosylate (SFN), a potent multikinase inhibitor, is used for the treatment of various cancers. However, it shows limited therapeutic applications due to its poor biopharmaceutical properties. The aim of the present investigation is to develop surface solid dispersion (SSD) of SFN using adsorbent to improve its solubility, bioavailability and therapeutic efficacy. Experimental approach: The SFN-SSD was prepared by modified solvent evaporation technique using Neusilin US2 (magnesium aluminometasilicate) as an adsorbent and sodium dodecyl sulphate as a surfactant. SFN-SSD was optimized by adopting the design of experiment (DOE) using 32 factorial designs and characterized in terms of in-vitro and in-vivo efficacy. Key results: The obtained SFN-SSD showed more than 20-fold improvement in SFN solubility. The FTIR depicted hydrogen bonding between SFN and Neusilin. Further, PXRD and DSC indicated the molecular dispersion of SFN to be amorphous. SFN-SSD and SFN immediate release tablets reflected cumulative release of 97.13 and 29.93 % in 1 h. The pharmacokinetics study of SFN-SSD showed 2 and 6.5-fold improvement in maximum concentration (Cmax,) and area under the curve (AUC0-t) as compared to pure SFN due to faster drug release at the absorption site. Conclusion: The study concluded that the SSD could be a scalable formulation approach and more industry-friendly technology to improve the biopharmaceutical properties of SFN.